The experiences and challenges of science and ethics : proceedings of an American-Iranian workshop (National Academies Press, 2003)
In April 2002, the U.S. National Academies hosted an interacademy workshop involving participants from the United States and Iran on the topic of Science and Ethics. The explicit purposes of the workshop were (a) to engage important members of the American and Iranian scientific communities in meaningful discussions of the topic of science and ethics and particularly differences in the approaches in the west and in Islamic countries in general and Iran in particular, (b) to encourage greater participation by Iranian scientists in international scientific discussions by exposing them to seasoned veterans in international meetings, and (c) to identify specific topics and approaches that could be carried out by the Academies in the two countries to contribute to international understanding of the importance of considering the ethical dimensions of scientific research and related activities. This report includes documents prepared by four breakout groups and a statement on priority areas for future interacademy cooperation developed at the final plenary session. Also included are background papers prepared by some participants prior to the workshop that were not previously published.